2022
DOI: 10.1108/ijm-06-2021-0363
|View full text |Cite
|
Sign up to set email alerts
|

Gender pay-gap: exploring the school-to-work transition of graduates in Italy

Abstract: PurposeIn this article, the authors study the gender pay-gap (GPG) among graduates in Italy (2011 cohort) who were employed four years after graduation. The authors focus on individuals who are new entering in the labour market or who match a low level of experience with a high level of education.Design/methodology/approachAimed at estimating the amount of the differential between male and female average wages, the authors have applied the Oaxaca–Blinder (O–B) decomposition. The results identify the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
2
1
0
Order By: Relevance
“…However, more than half of the gender wage gap remained unexplained. These findings reconfirm Ferri et al . (2021) results for Italy that the gender wage gap appeared right after graduation.…”
Section: Russiasupporting
confidence: 91%
See 2 more Smart Citations
“…However, more than half of the gender wage gap remained unexplained. These findings reconfirm Ferri et al . (2021) results for Italy that the gender wage gap appeared right after graduation.…”
Section: Russiasupporting
confidence: 91%
“…However, more than half of the gender wage gap remained unexplained. These findings reconfirm Ferri et al (2021) results for Italy that the gender wage gap appeared right after graduation. While the gap generally increased over time, quantile decomposition revealed that women experienced less pay gap inequality in low-paid jobs.…”
Section: Russiasupporting
confidence: 87%
See 1 more Smart Citation